2011
DOI: 10.1159/000329006
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Breast Care Nurses on Patients’ Satisfaction, Understanding of the Disease, and Adherence to Adjuvant Endocrine Therapy

Abstract: Background: Breast care nurses (BCNs) are specialized caregivers in certified breast cancer center teams. The impact of a BCN’s work remains unknown. Patients and Methods: The role of BCN care was evaluated in a post-discharge mail survey of 360 patients. Results: A total of 207 (87%) of 237 (66%) returned questionnaires were analyzed; 171 (83%) patients had BCN contact, 36 (17%) did not. The mean global quality of life scores (EORTC-QLQ-C30) were 66.3 for women with contact to a BCN versus 62.5 for women with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
22
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 10 publications
2
22
0
Order By: Relevance
“…Defining non-adherence as taking less than 80% medication, 93.4% were fully adherent. In line with other studies, it could be shown that patients who were more satisfied with information about potential problems with AET [10,11,17,23], understood and learned facts about AET [12,15,16,19,23], showed higher adherence. Being sufficiently informed about AET might help to feel prepared for potential side effects and to understand why they occur.…”
Section: Resultssupporting
confidence: 88%
See 1 more Smart Citation
“…Defining non-adherence as taking less than 80% medication, 93.4% were fully adherent. In line with other studies, it could be shown that patients who were more satisfied with information about potential problems with AET [10,11,17,23], understood and learned facts about AET [12,15,16,19,23], showed higher adherence. Being sufficiently informed about AET might help to feel prepared for potential side effects and to understand why they occur.…”
Section: Resultssupporting
confidence: 88%
“…Thus, the information fulfilled patients' informational needs. In line with other studies, this shows that most patients with breast cancer wish to receive as much and detailed medical information as possible, independent of valence of information . This result is highly relevant because receiving the right amount of information is related to treatment adherence .…”
Section: Resultssupporting
confidence: 88%
“…Even though a postsurgical contact nurse with specific expertise was mandated by the Swedish Association of Local Authorities in 2011, to date this has not been implemented by all care facilities, or for all patients with all types of cancer, such as patients with PC. Research has shown that nurses caring for patients with breast cancer have had a positive impact on patient recovery . Patients in our study were still struggling to come to terms with themselves in their everyday lives, which may indicate that the transition process was still incomplete for several patients.…”
Section: Discussionmentioning
confidence: 74%
“…An intervention focused on self-management of side-effects could potentially reduce the prevalence of nonadherence to and discontinuation of treatment. Others have suggested that health systems interventions utilizing oncology and/or advanced practice nurses may provide patients with the necessary support to achieve treatment completion [7579]. The current lack of such interventions represents a missed opportunity for health promotion.…”
Section: Discussionmentioning
confidence: 99%